1992
DOI: 10.1016/s0006-3495(92)81732-0
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties predicted by the ball and chain model of channel inactivation

Abstract: It has been proposed that part of a voltage gated channel is a tethered ball and that inactivation occurs when this wandering ball binds to a site in the channel. In order to be able to quantitatively test this model by comparison to experiments we developed analytical solutions and numerical simulations of the distribution of times it takes the ball to reach the binding site when the motion of the ball is random and when it is also influenced by a directed force. If the motion of the ball is one-dimensional, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…SHOWING YOUR ID 365 Importantly, this model offers a straightforward explanation of how timing of such channels can be regulated by the length of chain (or tether). The behavior of the ball and chain system was modeled by developing analytical solutions and numerical simulations of the distribution of the time it takes the wandering ball to reach the binding site when the motion of the ball is random (Liebovitch et al, 1992). It has been shown that this action can be described by a single exponential law with a rate constant inversely proportional to the square of the length of the chain (Liebovitch et al, 1992).…”
Section: Ball and Chain Modelmentioning
confidence: 99%
“…SHOWING YOUR ID 365 Importantly, this model offers a straightforward explanation of how timing of such channels can be regulated by the length of chain (or tether). The behavior of the ball and chain system was modeled by developing analytical solutions and numerical simulations of the distribution of the time it takes the wandering ball to reach the binding site when the motion of the ball is random (Liebovitch et al, 1992). It has been shown that this action can be described by a single exponential law with a rate constant inversely proportional to the square of the length of the chain (Liebovitch et al, 1992).…”
Section: Ball and Chain Modelmentioning
confidence: 99%
“…However, analysis of such mutations in Shaker and Kv1.4 K ϩ channels does not show such a clear trend. Some shortenings of the tether actually slow inactivation, suggesting that rather than being a simple tether, 20,33 this region may have some secondary or tertiary structure that constrains the movement and permissible orientations of the inactivation ball. (2) Events, such as drug binding, which occur at the extracellular mouth of the pore, do not alter N-type inactivation, whereas those that occur at the intracellular mouth of the pore do alter N-type inactivation.…”
Section: Properties and Mechanism Of N-type Inactivationmentioning
confidence: 99%
“…Moreover, in some cases, the kinetics of the processes occurring in ionic channels exhibits a dependence upon previous states (like the recovery of a sodium channel from slow inactivation), and consequently has a rather nonMarkovian character. An alternative approach to the modeling of the inactivation of a voltage-gated ionic channel via the ball and chain mechanism may be found in [5,6,16,17]. All these studies take as a starting point the hypothesis that the inactivation rate is controlled by the diffusion of an inactivating gate in the region, restricted by the length of its tether.…”
Section: The Physical Formulation Of the Ball And Chain Modelmentioning
confidence: 99%
“…Gating occurs through proper, reversible conformational changes induced by the action of stimuli that lead to the closing/plugging of the channel pore. This study was mostly inspired by earlier experimental and theoretical studies [3][4][5] on a special type of gating, called fast or N-type inactivation. It occurs in voltage-gated sodium and potassium channels.…”
Section: Introductionmentioning
confidence: 99%